Effect of Arteriovenous Anastomosis on Blood Pressure Reduction in Patients With Isolated Systolic Hypertension Compared With Combined Hypertension. Issue 12 (21st December 2016) - Ott, Christian; Lobo, Melvin D.; Sobotka, Paul A.; Mahfoud, Felix; Stanton, Alice; Cockcroft, John; Sulke, Neil; Dolan, Eamon; van der Giet, Markus; Hoyer, Joachim; Furniss, Stephen S.; Foran, John P.; et al.
Abstract : Background: Options for interventional therapy to lower blood pressure (BP) in patients with treatment‐resistant hypertension include renal denervation and the creation of an arteriovenous anastomosis using the ROX coupler. It has been shown that BP response after renal denervation is greater in patients with combined hypertension (CH) than in patients with isolated systolic hypertension (ISH). We analyzed the effect of ROX coupler implantation in patients with CH as compared with ISH. Methods and Results: The randomized, controlled, prospective ROX Control Hypertension Study included patients with true treatment‐resistant hypertension (office systolic BP ≥140 mm Hg, average daytime ambulatory BP ≥135/85 mm Hg, and treatment with ≥3 antihypertensive drugs including a diuretic). In a post hoc analysis, we stratified patients with CH (n=31) and ISH (n=11). Baseline office systolic BP (177±18 mm Hg versus 169±17 mm Hg, P =0.163) and 24‐hour ambulatory systolic BP (159±16 mm Hg versus 154±11 mm Hg, P =0.463) did not differ between patients with CH and those with ISH. ROX coupler implementation resulted in a significant reduction in office systolic BP (CH: −29±21 mm Hg versus ISH: −22±31 mm Hg, P =0.445) and 24‐hour ambulatory systolic BP (CH: −14±20 mm Hg versus ISH: −13±15 mm Hg, P =0.672), without significant differences between the two groups. The responder rate (office systolic BP reduction ≥10 mm Hg) after 6 months was not different (CH: 81% versus ISH: 82%, P =0.932). Conclusions: Our data suggest that creation of an arteriovenous anastomosis using the ROX coupler system leads to a similar reduction of office and 24‐hour ambulatory systolic BP in patients with combined and isolated systolic hypertension. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01642498.